2009
DOI: 10.1111/j.1551-2916.2009.03057.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex Impedance and Dielectric Dispersion in Carbon Fiber Reinforced Cement Matrices

Abstract: The electrical response of carbon fiber reinforced cement mortar over the frequency range 1 Hz–10MHz has been presented. The low frequency conductivity is shown to be directly influenced by increasing fiber dosage, with conductivity percolation occurring at dosages in the range 0.35%–1.0% (by volume). When viewed across the entire frequency spectrum, the conductivity and dielectric constant frequency dispersions reveal two regions of relaxation. The definition of these regions becomes more pronounced as the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…The incorporation of the rCF modifies the diagram as shown inFigure 16. Both the reactance and electrical resistance values decrease and the feature attributed to the electrode polarization effects is not discernible, as described by previous researchers(54).Ford et al (53) demonstrated that the Nyquist diagram of cementitious samples is affected by the inclusion of conductive phases. The emerging high-frequency arc that appears on the left side of the diagram is related to the bulk features of the sample.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The incorporation of the rCF modifies the diagram as shown inFigure 16. Both the reactance and electrical resistance values decrease and the feature attributed to the electrode polarization effects is not discernible, as described by previous researchers(54).Ford et al (53) demonstrated that the Nyquist diagram of cementitious samples is affected by the inclusion of conductive phases. The emerging high-frequency arc that appears on the left side of the diagram is related to the bulk features of the sample.…”
supporting
confidence: 54%
“…The Nyquist diagrams of cementitious materials with conductive inclusions normally exhibit three individual arc/features, accounting for the electrochemical reactions and product layer deposition at the electrodes and bulk-related features(53).Figure 15illustrates the Nyquist diagram for the neat UHPC concrete sample in which only two arcs can be observed. The spur element on the right side is related to the polarisation effects at the electrode(54). The rest of the diagram is part of the arc related to the bulk response of the sample.…”
mentioning
confidence: 99%
“…The mid arc is produced by a strong surface effect of double layer capacitance and surface resistance at the fibre-pore fluid interface (Schwarz, 1962;Schurr, 1964;Mason et al, 2002;Suryanto et al, 2016;Zhang et al, 2022). Most importantly, the bulk arc is the bulk response produced by the bulk conduction mechanism and the interfacial polarization (Christensen et al, 1994;McCarter et al, 2009). The bulk conductivity σ, as the parameter of interest in this study, situates at the transitional location where the double layer effect is diminished and the bulk response dominates (Zhang et al, 2022).…”
Section: Electrical Measurement 2311 Electrochemical Impedance Spectr...mentioning
confidence: 97%
“…Carbon materials have been extensively investigated, especially graphene and carbon nanotubes, for a great variety of applications such as optical devices, electrodes, biosensors, as filler to reinforce materials, , or conductive composites. Conductive coatings based on these carbon materials have also been further investigated. However, the conductive coatings are usually thick films composed of a polymer host with the conductive filler (graphene or carbon nanofibers) providing resistivities of 10 –1 –10 –3 Ω m. Carbon black is a conductive filler with a wide particle size distribution (10 nm to 100 μm) , which is mainly used as rubber filler or reinforcement in paints, polymers, or gums .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials have been extensively investigated, especially graphene and carbon nanotubes, for a great variety of applications such as optical devices, 1 electrodes, 2 biosensors, 3 as filler to reinforce materials, 4,5 or conductive composites. 6−8 Conductive coatings based on these carbon materials have also been further investigated.…”
Section: Introductionmentioning
confidence: 99%